A nitrogen-doped CuSe / MoSe composite catalyst, a preparation method and use thereof

CN123005441APending Publication Date: 2026-10-30CHINA JILIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611312232.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

本发明旨在解决现有非贵金属硒化物催化剂存在的材料本征电导率较低、活性位点类型单一且暴露不充分、单一组分体系内部界面电荷分离效率低下的问题

Benefits of technology

1. 本发明通过水合肼与氮气热处理这两个步骤引入氮源,实现氮元素的均匀掺杂,优化了材料的电子结构,提高了催化剂的电导率和催化活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123005441A_ABST
    Figure CN123005441A_ABST
Patent Text Reader

Abstract

The application discloses a nitrogen-doped CuSe / MoSe composite catalyst and a preparation method thereof, and application of the nitrogen-doped CuSe / MoSe composite catalyst in an electrocatalytic hydrogen evolution reaction. The preparation method comprises the following steps: mixing a copper source, a selenium source, a molybdenum source and hydrazine hydrate in water, stirring to form a precursor solution; performing a solvothermal reaction on the precursor solution to obtain a CuSe / MoSe precursor; and performing heat treatment on the CuSe / MoSe precursor under a nitrogen atmosphere to obtain the nitrogen-doped CuSe / MoSe composite catalyst. The CuSe / MoSe nanocomposite material with a heterostructure is constructed through a hydrothermal reaction, and nitrogen is introduced through high-temperature nitridation treatment, so that the nitrogen is uniformly doped at the interface of CuSe and MoSe, the electronic structure of the material is effectively controlled, and the electrical conductivity and intrinsic catalytic activity are improved. The heterojunction interface formed between CuSe and MoSe in the composite catalyst is beneficial to interface charge transfer, and the reaction kinetics and catalytic stability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, particularly to catalysts for hydrogen evolution reaction, specifically to a nitrogen-doped CuSe / MoSe composite catalyst and its preparation method, as well as the use of the catalyst in electrocatalytic hydrogen evolution reaction. Background Technology

[0002] Hydrogen, as a clean, carbon-free, and recyclable secondary energy carrier, boasts advantages such as high energy density, ease of storage and transportation, and efficient electrochemical conversion into electricity in fuel cells. It is widely regarded as a crucial component of future sustainable energy systems. Its green, low-carbon, abundant, and high calorific value make it a significant potential application in large-scale, long-cycle energy storage, renewable energy storage and transportation, and system integration, serving as a key support for achieving energy structure transformation.

[0003] Currently, platinum (Pt)-based and platinum alloy catalysts, widely used in proton exchange membrane water electrolysis, exhibit excellent electrocatalytic activity in the hydrogen evolution reaction (HER). However, their high cost and resource scarcity severely restrict the economic feasibility and sustainability of related technologies in large-scale industrial plants. Therefore, developing alternative non-precious metal electrocatalysts with high activity, long-term stability, and low cost has become one of the key scientific issues for promoting the practical application of hydrogen energy technology. In recent years, researchers have focused on constructing composite catalysts and utilizing structural design strategies such as heterojunction interfaces, lattice defects, and synergistic electronic effects to effectively increase the density of active sites and enhance the intrinsic activity of individual sites, thereby optimizing the overall catalytic performance. Such non-precious metal-based composite catalytic systems provide a feasible path to overcome the bottleneck of precious metal resources and achieve efficient and economical HER electrode materials.

[0004] However, existing non-precious metal selenide catalysts still face several key technical limitations under practical application conditions: First, the intrinsic conductivity of the materials is low, resulting in significant polarization loss at high current densities, making it difficult to meet the high-power operation requirements of industrial electrolyzers; Second, catalysts prepared by traditional synthesis methods are prone to nanoparticle aggregation, with single active site types and insufficient exposure, limiting the synergistic optimization of multi-step reaction pathways; Third, the interfacial charge separation efficiency within a single-component system is low, and the surface migration barrier of reaction intermediates is high, restricting the overall hydrogen evolution reaction kinetic efficiency. Summary of the Invention

[0005] (a) Technical problems to be solved The present invention aims to solve the problems of low intrinsic conductivity of existing non-precious metal selenide catalysts, single type of active site and insufficient exposure, and low efficiency of interfacial charge separation in single-component systems.

[0006] (II) Technical Solution To address the aforementioned technical problems, this invention proposes a method for preparing a nitrogen-doped CuSe / MoSe composite catalyst, comprising the following steps: S1. Mix copper source, selenium source, molybdenum source and hydrazine hydrate in water and stir to form a precursor solution; S2. The precursor solution is subjected to a solvothermal reaction to obtain the CuSe / MoSe precursor; S3. The CuSe / MoSe precursor is heat-treated in a gas atmosphere to obtain a nitrogen-doped CuSe / MoSe composite catalyst.

[0007] According to a preferred embodiment of the present invention, the copper source is CuCl2·2H2O, the selenium source is Se powder, and the molybdenum source is Na2MoO4.

[0008] According to a preferred embodiment of the present invention, the molar ratio of copper to molybdenum in the precursor solution in step S1 is 1:19 to 1:3.

[0009] According to a preferred embodiment of the present invention, the temperature of the solvothermal reaction in step S2 is 160.0 °C to 240.0 °C, and the time is 6.0 hours to 12.0 hours.

[0010] According to a preferred embodiment of the present invention, the heat treatment temperature in step S3 is 300.0 ℃ to 600.0 ℃, the time is 2.0 hours to 4.0 hours, and the atmosphere gas is nitrogen.

[0011] The present invention also proposes a nitrogen-doped CuSe / MoSe composite catalyst, which is prepared by the above-described method for preparing nitrogen-doped CuSe / MoSe composite catalyst.

[0012] According to a preferred embodiment of the present invention, the nitrogen-doped CuSe / MoSe composite catalyst has a CuSe / MoSe heterostructure, with nitrogen uniformly doped at the interface between CuSe and MoSe.

[0013] This invention also proposes the use of nitrogen-doped CuSe / MoSe composite catalysts in electrocatalytic hydrogen evolution reactions, wherein the nitrogen-doped CuSe / MoSe composite catalysts have CuSe / MoSe heterostructures, and nitrogen is uniformly doped at the interface between CuSe and MoSe.

[0014] According to a preferred embodiment of the present invention, the composite catalyst is used as a cathode catalyst for hydrogen production via acidic or alkaline water electrolysis.

[0015] (III) Beneficial Effects The nitrogen-doped CuSe / MoSe composite catalyst provided by this invention has the following beneficial effects: 1. This invention introduces a nitrogen source through two steps: hydrazine hydrate and nitrogen heat treatment, thereby achieving uniform doping of nitrogen, optimizing the electronic structure of the material, and improving the conductivity and catalytic activity of the catalyst.

[0016] 2. The CuSe and MoSe of the present invention form a heterostructure, which enhances interfacial charge transfer and improves reaction kinetics and catalytic stability.

[0017] 3. The preparation method of this invention is simple, reproducible, and suitable for large-scale production, and has potential application prospects in the field of hydrogen production by water electrolysis. Attached Figure Description

[0018] Figure 1 This is a SEM image of the nitrogen-doped CuSe / MoSe composite catalyst of Example 3 of the present invention; Figure 2 The energy dispersive X-ray spectrum of the nitrogen-doped CuSe / MoSe composite catalyst in Example 3 of this invention is shown below. Figure 3 This is a TEM image of the nitrogen-doped CuSe / MoSe composite catalyst in Example 3 of this invention; Figure 4 The XRD pattern of the nitrogen-doped CuSe / MoSe composite catalyst in Example 3 of this invention is shown below. Figure 5 The linear voltammetric curves of the nitrogen-doped CuSe / MoSe composite catalyst in Example 3 of this invention and those of Comparative Examples 1 and 2 are shown. Detailed Implementation

[0019] The nitrogen-doped CuSe / MoSe composite catalyst proposed in this invention constructs a nanostructure with high electrocatalytic hydrogen evolution activity through a simple hydrothermal reaction, and then further improves the electrocatalytic active sites and enhances the electrocatalytic hydrogen evolution activity through a high-temperature nitrogen gas heat treatment method.

[0020] In this invention, CuSe / MoSe refers to a mixture containing both CuSe and MoSe, typically a mixture of multiple crystal forms. In this invention, CuSe generally refers to copper selenides, and MoSe generally refers to molybdenum selenides; neither refers to a specific elemental ratio or crystal form. In actual catalysts, both copper and molybdenum selenides may contain multiple crystal forms. This invention can change the crystal form in CuSe / MoSe by adjusting the ratio of raw materials and the reaction temperature. In the following examples, for MoSe, the predominantly formed crystal form is Mo... 15 Se 19 It is mainly composed of Cu, and may also contain a certain amount of MoSe2. For CuSe, the main crystal form is CuSe(Cu) 2+ and Se 2-The main crystal form is the one with a ratio of 1:1.

[0021] In this invention, hydrazine hydrate provides the necessary reducing environment for the reaction and participates in the initial nitrogen doping of the surface and the loosening of the structure; nitrogen heat treatment is responsible for further loosening of the structure, nitriding of the precursor, and activation of electrocatalytic active sites. Nitrogen doping effectively modulates the band structure, increases the Fermi level density of states, optimizes the d-band center position, and enhances charge transfer efficiency in conjunction with the heterointerface, thereby systematically improving the intrinsic conductivity and catalytic activity of the material at the electronic structure level.

[0022] Specifically, the preparation method of the nitrogen-doped CuSe / MoSe composite catalyst provided by the present invention includes the following steps: S1. Mix copper source, selenium source, molybdenum source and hydrazine hydrate in water and stir to form a precursor solution; S2. The precursor solution is subjected to a solvothermal reaction to obtain the CuSe / MoSe precursor; S3. The CuSe / MoSe precursor is heat-treated under a nitrogen atmosphere to obtain a nitrogen-doped CuSe / MoSe composite catalyst.

[0023] The following description uses specific embodiments and accompanying drawings. Example 1

[0024] S1. Preparation of precursor solution.

[0025] In Example 1, 1.0 mmol of CuCl2·2H2O, 4.0 mmol of Se powder, 3.0 mmol of Na2MoO4, and 10.0 ml of hydrazine hydrate were stirred and mixed for 0.5 hours to obtain a precursor solution.

[0026] In the hydrothermal reaction below, hydrazine hydrate provides the reduction reaction environment, while the ammonia and amino groups produced by the decomposition of hydrazine hydrate are adsorbed on the catalyst surface, providing a nitrogen source for nitrogen doping during heat treatment.

[0027] S2. The CuSe / MoSe precursor is obtained through a hydrothermal reaction.

[0028] In this step, the precursor solution is placed in a high-pressure reactor for a solvothermal reaction, with parameters controlled at 220°C and 12.0 hours. After washing and drying, the CuSe / MoSe precursor is obtained, wherein the molar ratio of copper to molybdenum is 1:3.

[0029] The hydrothermal reaction mechanism is as follows: hydrazine hydrate not only acts as a reducing agent to rapidly reduce the selenium source to highly reactive Se, but also... 2- Ions, inducing CuSe and Mo 15 Se 19Alternatively, MoSe2 may undergo in-situ nucleation and crystallization; the gas produced by its thermal decomposition also acts as a template for pore formation, resulting in a loose and porous structure; simultaneously, the two phases precipitate sequentially due to the difference in solubility product, allowing Mo... 15 Se 19 Alternatively, MoSe2 can be epitaxially grown directly on the CuSe surface, thus spontaneously forming a heterojunction interface.

[0030] S3, nitrogen heat treatment.

[0031] CuSe / MoSe was placed in a ceramic boat on the downstream side of a tube furnace, and the tube furnace was heated to 300.0℃ at 5.0℃ / min and maintained in a N2 atmosphere for 2.0 hours to obtain nitrogen-doped CuSe / MoSe, wherein the molar ratio of copper to molybdenum was 1:3.

[0032] During the heat treatment process, the hydroxyl groups and other oxygen-containing functional groups adsorbed on the catalyst surface will volatilize or undergo thermal decomposition, thus fully exposing the active sites; at the same time, the ammonia or amino groups adsorbed on the catalyst surface will be incorporated into the catalyst, thereby nitriding the catalyst. Example 2

[0033] The steps of Example 2 are basically the same as those of Example 1. The main difference between Example 2 and Example 1 is that the composition of the precursor solution prepared in step S1 is different. Specifically, it is: 0.8 mmol CuCl2·2H2O, 4.0 mmol Se powder, and 3.2 mmol Na2MoO4. The molar ratio of copper to molybdenum in the nitrogen-doped CuSe / MoSe obtained in Example 2 is 1:4. Example 3

[0034] The steps in Example 3 are basically the same as those in Example 1. The main difference between Example 3 and Example 1 is that the composition of the precursor solution prepared in step S1 is different, specifically: 0.6 mmol CuCl2·2H2O, 4.0 mmol Se powder, and 3.4 mmol Na2MoO4. The remaining steps are the same as in Example 1. The final molar ratio of copper to molybdenum in the nitrogen-doped CuSe / MoSe obtained in Example 3 is 1:5.67. Example 4

[0035] The steps in Example 4 are basically the same as those in Example 1. The main difference between Example 4 and Example 1 is that the composition of the precursor solution prepared in step S1 is different, specifically: 0.4 mmol CuCl2·2H2O, 4.0 mmol Se powder, and 3.6 mmol Na2MoO4. The remaining steps are the same as in Example 1. The final nitrogen-doped CuSe / MoSe has a copper to molybdenum molar ratio of 1:9. Example 5

[0036] The steps in Example 5 are basically the same as those in Example 1. The main difference between Example 5 and Example 1 is that the composition of the precursor solution prepared in step S1 is different, specifically: 0.2 mmol CuCl2·2H2O, 4 mmol Se powder, and 3.8 mmol Na2MoO4. The remaining steps are the same as in Example 1. The final nitrogen-doped CuSe / MoSe has a copper to molybdenum molar ratio of 1:19. Example 6

[0037] The steps of Example 6 are basically the same as those of Example 3. The main difference between Example 6 and Example 3 is the hydrothermal reaction temperature in step S2, which is 160.0 °C. Example 7

[0038] The steps of Example 7 are basically the same as those of Example 3. The main difference between Example 7 and Example 3 is the hydrothermal reaction temperature in step S2, which is 180.0 °C. Example 8

[0039] The steps of Example 8 are basically the same as those of Example 3. The main difference between Example 8 and Example 3 is the hydrothermal reaction temperature in step S2, which is 200.0 °C. Example 9

[0040] The steps of Example 9 are basically the same as those of Example 3. The main difference between Example 9 and Example 3 is the hydrothermal reaction temperature in step S2, which is 240.0 °C. Comparative Example 1

[0041] The steps of Comparative Example 1 are the same as those of Example 1. The main difference between Comparative Example 1 and Example 1 is that no molybdenum source (Na2MoO4) is added during the preparation process. The remaining steps are the same as those of Example 1, and pure phase CuSe is finally obtained. Comparative Example 2

[0042] The steps of Comparative Example 2 were also the same as those of Example 1. The main difference between Comparative Example 2 and Example 1 was that no copper source (CuCl2·2H2O) was added during the preparation process. The remaining steps were the same as those of Example 1, and pure phase MoSe was obtained.

[0043] Electrode preparation:

[0044] The glassy carbon electrode used in the comparative examples and embodiments of this invention has a diameter of 4.0 mm; the catalyst suspension was prepared by mixing 12.0 mg of catalyst sample, 15.0 μL of 5.0 wt.% Nafion ethanol solution, 0.5 mL of ethanol and 0.5 mL of deionized water.

[0045] Characterization results:

[0046] Table 1: Comparison of electrocatalytic hydrogen evolution activity of catalysts in Examples 1-9 and Comparative Examples 1 and 2 of the present invention Comparative Example 1 / Example 5 345.0 Comparative Example 2 258.0 Example 6 321.0 Example 1 343.0 Example 7 311.0 Example 2 254.0 Example 8 309.0 Example 3 222.0 Example 9 244.0 Example 4 342.0 Figure 1 This is the nitrogen-doped CuSe / MoSe composite catalyst of Example 3 of the present invention. From... Figure 1 The SEM images show that the catalyst surface in Example 3 exhibits a rough, granular aggregate morphology, with a relatively uniform distribution and a loose, porous structure. This structure is beneficial for increasing the specific surface area of ​​the material, thereby exposing more electrochemical catalytic active sites.

[0047] Figure 2 This is the energy-dispersive X-ray spectrum of the nitrogen-doped CuSe / MoSe composite catalyst of Example 3 of the present invention. As shown in the figure, the composite catalyst contains Se, Mo, Cu, N, and O elements. The presence of O may be attributed to slight oxidation of the catalyst material surface in air.

[0048] Figure 3 This is a TEM image of the nitrogen-doped CuSe / MoSe composite catalyst from Example 3 of this invention. Figure 3 As can be seen, the nitrogen-doped CuSe / MoSe composite catalyst in Example 3 of this invention has obvious lattice stripe characteristics. Figure 3 The area within the red box and its magnified view show clearly visible lattice fringe spacings of approximately 0.117 nm and 0.268 nm, respectively, representing Mo... 15 Se 19 The (012) of Mo and the (011) of CuSe indicate that the catalyst has excellent crystallinity. 15 Se 19 It is in close contact with both Cu and Se crystalline phases, forming a heterojunction interface at their boundary. Due to Mo... 15 Se 19 Unlike CuSe, the Fermi level of the catalyst differs. Upon interfacial contact, electrons undergo a directional transfer from the phase with the higher Fermi level to the phase with the lower Fermi level until the two phases reach equilibrium. This creates a built-in electric field in the interfacial region and induces charge redistribution. This built-in electric field effectively promotes the directional transfer of electrons between the catalyst and reactant molecules, reducing interfacial charge transfer resistance. Simultaneously, charge redistribution modulates the adsorption free energy of active sites for reaction intermediates (such as H*), bringing it closer to the optimal adsorption strength for the hydrogen evolution reaction. These synergistic effects significantly enhance the intrinsic electrocatalytic activity of the catalyst, specifically manifested in a decrease in overpotential, a reduction in Tafel slope, and a decrease in charge transfer resistance.

[0049] Figure 4The image shows the XRD pattern of the nitrogen-doped CuSe / MoSe composite catalyst of Example 3 of this invention. Figure 4 As can be seen, two main sets of diffraction peaks were detected in the spectrum, corresponding to Mo respectively. 15 Se 19 The standard cards for CuSe (PDF#38-0986) and CuSe (PDF#27-0184) were used. No obvious impurity diffraction peaks appeared in the spectra, and the strong diffraction signals indicated that the obtained product was a crystalline phase with high purity. (Summary) Figure 3 and Figure 4 The test results show that in the nitrogen-doped CuSe / MoSe composite catalyst prepared in this invention, Mo... 15 Se 19 The coexistence of the CuSe phase and the formation of a heterojunction interface are beneficial to improving the electron transfer efficiency and electrocatalytic performance of the material.

[0050] Figure 5 The image shows the linear voltammetric curves of the nitrogen-doped CuSe / MoSe composite catalyst in Example 3 of this invention and those of Comparative Examples 1 and 2. A three-electrode system was constructed using the electrodes prepared in Example 3 and Comparative Examples 1 and 2 as the working electrode, a graphite rod as the counter electrode, and silver / silver chloride as the reference electrode. The hydrogen evolution electrocatalytic activity of each electrode was tested in a 0.5 mol / L H₂SO₄ solution. Figure 5 It can be seen that at a current density of 10.0 mA / cm² 2 At that time, the nitrogen-doped CuSe / MoSe (Cu:Mo = 1:5.67, 220.0℃) in Example 3 exhibited the best electrocatalytic hydrogen evolution performance. Table 1 shows its μ... 10 =222.0 mV, indicating that the preparation method of the present invention effectively reduces the overpotential of electrocatalytic hydrogen evolution and improves the catalytic activity of the catalyst.

[0051] Furthermore, the hydrogen evolution catalytic performance of Example 3 was compared with recently disclosed transition metal chalcogenide electrocatalysts. Dongre et al. (DOI: 10.1016 / j.mtsust.2024.100894) reported a Cu-Mo bimetallic thioselenide nanocomposite material (CuMoSSe) that achieved 10.0 mA / cm² in acidic media. 2 The overpotential at the current density was 290.0 mV. In contrast, Example 3 of the present invention required only 220.0 mV overpotential under the same test conditions, indicating that the preparation method of the present invention effectively reduces the overpotential of electrocatalytic hydrogen evolution and has certain performance advantages.

[0052] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a nitrogen-doped CuSe / MoSe composite catalyst, characterized in that, Includes the following steps: S1. Mix copper source, selenium source, molybdenum source and hydrazine hydrate in water and stir to form a precursor solution; S2. The precursor solution is subjected to a solvothermal reaction to obtain the CuSe / MoSe precursor; S3. The CuSe / MoSe precursor is heat-treated in a gas atmosphere to obtain a nitrogen-doped CuSe / MoSe composite catalyst.

2. The method for preparing the nitrogen-doped CuSe / MoSe composite catalyst according to claim 1, characterized in that: The copper source is CuCl2·2H2O, the selenium source is Se powder, and the molybdenum source is Na2MoO4.

3. The preparation method according to claim 1, characterized in that: The molar ratio of copper to molybdenum in the precursor solution in step S1 is 1:19 to 1:

3.

4. The method for preparing the nitrogen-doped CuSe / MoSe composite catalyst according to claim 1, characterized in that: In step S2, the temperature of the solvothermal reaction is 160.0 ℃ to 240.0 ℃, and the time is 6.0 hours to 12.0 hours.

5. The method for preparing the nitrogen-doped CuSe / MoSe composite catalyst according to claim 1, characterized in that, In step S3, the heat treatment temperature is 300.0℃~600.0℃, the time is 2.0 hours~4.0 hours, and the atmosphere gas is nitrogen.

6. A nitrogen-doped CuSe / MoSe composite catalyst, characterized in that, It is prepared by the method described in any one of claims 1 to 5 for the preparation of nitrogen-doped CuSe / MoSe composite catalyst.

7. The nitrogen-doped CuSe / MoSe composite catalyst according to claim 6, characterized in that, It has a CuSe / MoSe heterostructure, with nitrogen uniformly doped at the interface between CuSe and MoSe.

8. The use of a nitrogen-doped CuSe / MoSe composite catalyst in the electrocatalytic hydrogen evolution reaction, characterized in that, The nitrogen-doped CuSe / MoSe composite catalyst is the nitrogen-doped CuSe / MoSe composite catalyst according to claim 6.

9. The use of the nitrogen-doped CuSe / MoSe composite catalyst according to claim 8 in the electrocatalytic hydrogen evolution reaction, characterized in that: The nitrogen-doped CuSe / MoSe composite catalyst has a CuSe / MoSe heterostructure, with nitrogen uniformly doped at the interface between CuSe and MoSe.

10. The use of the nitrogen-doped CuSe / MoSe composite catalyst according to claim 8 in the electrocatalytic hydrogen evolution reaction, characterized in that: The composite catalyst is used as a cathode catalyst for hydrogen production via acidic or alkaline water electrolysis.